Immunological signatures of candida-associated urinary tract infections in urolithiasis: Role of interleukins and complement components - Ban Badran Adnan; Ayad M. Gaidan; Hawazin Ahmed Abid (Ukrainian Journal of Nephrology and Dialysis, 2025)
Urinary tract infections (UTIs) are prevalent among individuals with urolithiasis. Bacterial pathogens are commonly associated with UTIs; however, fungal infections are increasingly recognised, particularly in patients with pre-existing urological abnormalities.The present cross-sectional study aimed to investigate the relationship between UTIs caused by Candida species (Candida spp.) and selected interleukins (ILs) and complement component 2 (C2) and 4 (C4) in patients with urolithiasis.Methods. One hundred urine samples were collected from patients with urolithiasis and twenty urine samples from healthy individuals (controls). Candida spp. were detected in 47% of the urine samples from patients (versus none in the control group), based on growth characteristics on Sabouraud dextrose agar (SDA) and staining with Gram stain and lactophenol cotton blue (LPCB). Urine levels of IL-6, IL-17, IL-22, C2, and C4 were measured using commercially available ELISA assay kits.Results. The most common species was Candida albicans (C. albicans) (59.5%), while the least common was Candida krusei (C. krusei) (6.3%). Levels of IL-6, IL-17 and IL-22 were significantly increased (P < 0.05) in urolithiasis patients (19.6 ± 2.4 pg/ml, 77.8 ± 16.34 pg/ml and 93.5 ± 11.9 pg/ml, respectively) compared with the control group (11.5 ± 3.7 pg/ml, 22.5 ± 6.41 pg/ml and 38.6 ± 9.4 pg/ml, respectively). Levels of C2 were significantly reduced (P < 0.05) in patients compared with the control group (51.03 ± 9.44 ng/ml vs. 195.21 ± 13.8 ng/ml).Conclusions. The obtained data indicate that Candida-associated UTIs in patients with urolithiasis are accompanied by a pronounced local immune response and may worsen the course of the underlying disease. Measurement of urinary levels of IL-6, IL-17, IL-22, and C2 may be useful as additional biomarkers of Candida infection and the intensity of the inflammatory process. These markers could potentially improve diagnosis and risk stratification of complications in this patient population.